2006
DOI: 10.1007/s11010-006-0639-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular inosine participates in tumor necrosis factor-alpha induced nitric oxide production in cultured Sertoli cells

Abstract: Recent reports have described purinergic modulation of tumor necrosis factor-alpha (TNF-alpha) signaling in neutrophils and astrocytes. In Sertoli cells, both TNF-R1 and TNF-R2 TNF-alpha receptors are present and this cytokine modulates many functions of these cells related to the maintenance of spermatogenesis. Sertoli cells express distinct purinoreceptors and previous work has shown that these cells secrete extracellular nucleotides and their metabolites. In this work, we studied the possible role of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…CAMP responsive element (CRE) and activator protein complex (AP1) have been identified in gal‐3 promoter, an observation which is compatible with the potential direct stimulatory actions of FSH and EGF, respectively, as reported here. Nuclear factor κ B (NF‐ κ B) binding site has been reported in gal‐1 but not in gal‐3 promoter meaning that TNF‐ α effect reported here on Gal‐3 expression is probably exerted in an indirect manner and/or is exerted via another signalling pathway such as, for example, the ERK1/2 and p38 MAPK pathway (de Souza et al. , 2006).…”
Section: Discussionmentioning
confidence: 84%
“…CAMP responsive element (CRE) and activator protein complex (AP1) have been identified in gal‐3 promoter, an observation which is compatible with the potential direct stimulatory actions of FSH and EGF, respectively, as reported here. Nuclear factor κ B (NF‐ κ B) binding site has been reported in gal‐1 but not in gal‐3 promoter meaning that TNF‐ α effect reported here on Gal‐3 expression is probably exerted in an indirect manner and/or is exerted via another signalling pathway such as, for example, the ERK1/2 and p38 MAPK pathway (de Souza et al. , 2006).…”
Section: Discussionmentioning
confidence: 84%
“…Nitric oxide production was assayed by quantification of the stable end product of nitric oxide oxidation -nitrite (NO 2 − ) -as previously described (Souza et al, 2006). Briefly, the incubation medium of peritoneal or RAW 264.7 macrophages were collected after the treatments and centrifuged at 12,000 ×g for 10 min.…”
Section: Nitrite Assaymentioning
confidence: 99%
“…[88][89][90] Extracellular inosine acts as intermediary in tumor necrosis factor-α stimulated nitric oxide production in cultured Sertoli cells. 91 Inosine can suppress the activity of intracellular lactate dehydrogenase (LDH), thus blocking the major source of energy supply of cancer cells. 92 Some studies have reported its inhibitory effect on breast cancer, 93 liver cancer, 94 prostate cancer, 83 and colon cancer.…”
Section: Discussionmentioning
confidence: 99%